COVID-19 in socially vulnerable quilombola populations in Salvaterra, Pará, Eastern Amazon, Brazil - Nelson Veiga Gonçalves; João Simão de Melo Neto; Selma Kazumi da Trindade Noguchi; Andrey Silva Machado; Alcindo da Silva Martins Junior; Maira Cibelle da Silva Peixoto; Alba Lúcia Ribeiro Raithy; Camylle Maia Costa Faria; Tainara Carvalho Garcia Miranda Filgueiras; Alex Baima Amaral Júnior; Claudia do Socorro Carvalho Miranda (Journal of Infection in Developing Countries)
Introduction: COVID-19 is a severe respiratory syndrome caused by the SARS-CoV-2 virus. In Brazil the highest infection rates are associated with socially vulnerable populations. This study therefore sought to analyze the spatial distribution of the disease and its relation with geographic, socioeconomic and public health policy characteristics associated with quilombola communities in Salvaterra municipality, state of Pará, for the period of March to September, 2020.